STRUCTURE SOCIAL PROBLEM COVID-19 THE PRACTICE OF - ONLINE LEARNING IN INDONESIAN HIGHER EDUCATION - Sardjuningsih Sardjuningsih; Moh. Shofiyul Huda MF (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
The COVID-19 crisis has effected a radical shift in the learning process, with conventional approaches giving way to online learning. Such an approach necessitates appropriate infrastructure and sufficient human resources. This study seeks to show the failure of suddenly implementing online learning in an emergency. This study employs a qualitative descriptive approach by collecting data through online interviews with students and lecturers at the Kediri Institute of Islamic Studies. It finds that online education has reduced students and lecturers' independence owing to three factors. First, institutions' bureaucratic procurement channels and limited funding allocation have resulted in unmet infrastructural needs. Second, lecturers have not been prepared to adapt to online learning, which requires different attitudes and competencies than conventional learning. Third, students and their families have been unable to handle the expense of internet access in their rural homes, where such infrastructure is limited. This study recommends a more comprehensive study that contrasts the effects of COVID-19 on different types of schools and social class as this would provide a strong basis for evaluating the government's ability to continue providing education in emergencies.